A typological study of Voice Onset Time (VOT) in Indo-Iranian languages. (November 2018) - Hussain, Qandeel
Highlights: VOT distinguishes the voiceless (un)aspirated categories from voiced (un)aspirated categories. Voiced (un)aspirated and implosive categories are not reliably differentiated by VOT. Retroflex stops exhibit shorter VOT than labial, dental, palatal, and velar stops. Abstract: The stop consonants of Indo-Iranian languages are categorized into two to maximum five laryngeal categories. The present study investigates whether Voice Onset Time (VOT) reliably differentiates the word-initial stop laryngeal categories and how it covaries with different places of articulation in ten languages (two Iranian: Pashto and Wakhi; seven Indo-Aryan: Dawoodi, Punjabi, Shina, Jangli, Urdu, Sindhi, and Siraiki; and one Isolate: Burushaski). The results indicated that there was a clear VOT distinction between the voiceless unaspirated and voiceless aspirated stops. The voiceless unaspirated stops showed shorter voicing lag VOTs than voiceless aspirated stops. Voiced unaspirated, voiced aspirated, and voiced implosive stops were characterized by voicing lead VOTs. In the voiceless unaspirated and aspirated categories, palatal affricates showed the longest voicing lag VOT due to the frication interval of this stop type. In contrast, voiceless unaspirated retroflex stops were characterized by the shortest voicing lag VOT. There were no clear place differences in the voiceless aspirated, voiced unaspirated, voiced aspirated, and voiced implosive categories. The findings of the current study suggest that VOT reliably differentiates the stop consonants of all the languages that contrast two (voiceless unaspirated vs. voiced unaspirated: Pashto and Wakhi) or three (voiceless unaspirated vs. voiceless aspirated vs. voiced unaspirated: Burushaski, Dawoodi, Punjabi, and Shina) laryngeal categories. However, VOT does not consistently distinguish the stop consonants of languages (Jangli, Urdu, Sindhi, and Siraiki) with contrastive voiced unaspirated, voiced aspirated, and voiced implosive categories.